Germline variation at 8q24 and prostate cancer risk in men of European ancestry - Marco Matejcic (Nature Portfolio, 2018)
Chromosome 8q24 is known to be a major susceptibility region for prostate cancer risk. Here the authors analyze genetic data across the 8q24 region from 71,535 prostate cancer patients identifying 12 risk loci, three previously unreported, highlighting the contribution of germline variation at this locus.